2022
DOI: 10.3389/fnut.2022.1036025
|View full text |Cite
|
Sign up to set email alerts
|

Different dissipation potential and dietary risk assessment of tristyrylphenol ethoxylates in cowpea ecosystem in China

Abstract: Tristyrylphenol ethoxylates (TSPEOn) are widely used as inert ingredients in pesticide formulations in the world. However, the information on the dissipation behavior of different homologs TSPEOn in agro-products is lacking. To investigate the dissipation behavior of TSPEOn, a cowpea field experiment treated with TSPEOn at different doses was carried out in Guangdong province, China. Different 24 TSPEO homologs were all detected in cowpea from the field terminal residue experiments, and the total concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several studies have found that pesticides are widespread in cowpeas based on market monitoring samples ( Cui et al, 2021 , Duan et al, 2016 , Luo et al, 2023 , Zhang et al, 2022 ). Some studies have reported the residue behaviour and dietary risk assessment of pesticides in cowpeas using field experiments ( Fu et al, 2020 , Li et al, 2022 , Li et al, 2022 , Wang et al, 2021 ). However, only a few studies have compared the residue differences in cowpeas under greenhouse and open-field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that pesticides are widespread in cowpeas based on market monitoring samples ( Cui et al, 2021 , Duan et al, 2016 , Luo et al, 2023 , Zhang et al, 2022 ). Some studies have reported the residue behaviour and dietary risk assessment of pesticides in cowpeas using field experiments ( Fu et al, 2020 , Li et al, 2022 , Li et al, 2022 , Wang et al, 2021 ). However, only a few studies have compared the residue differences in cowpeas under greenhouse and open-field conditions.…”
Section: Introductionmentioning
confidence: 99%